Success Factor of Entrepreneurship - Irmawati Irmawati; Mabrurok Mabrurok; Sri Murwanti; Edy Purwo Saputroi; Dewi Probowati Setyaningrum (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Entrepreneurship is an important issue because the findings of a number of studies show mixed results. In this regard, the identification of successful entrepreneurial factors becomes a reference for mapping important aspects of entrepreneurship itself. The purpose of this research is to examine the success of entrepreneurial factors using purpose sampling consisting of 200 female students. The results show that the variables of knowledge, capital and social factors have a positive effect on the success of entrepreneurial factors. Discussions and limitations are presented so that they become a reference for further research